2016
DOI: 10.1016/j.foodres.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Roles for dietary fibre in the upper GI tract: The importance of viscosity

Abstract: Dietary fibre has long been recognized as healthy because of its prebiotic quality and a number of dietary fibres, especially beta glucan have been shown to lower levels of circulating LDL cholesterol. However, although EFSA allow health claims to be made for this, there is no fundamental understanding of the detailed mechanism involved. More recently dietary fibre has been shown to have a range of functionality in the upper GI tract. The presence of fibre can alter gastric emptying thus affecting fullness and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 21 publications
0
31
0
2
Order By: Relevance
“…Alginate fluorescent labelling was carried out following the literature [59]. Sodium alginate (10 mg cm −3 ) was solubilized in sodium bicarbonate (50 mM) and 1.0 M NaOH was used to adjust the pH to 9.…”
Section: Synthesis Of Dtaf Labeled Sodium Alginatementioning
confidence: 99%
“…Alginate fluorescent labelling was carried out following the literature [59]. Sodium alginate (10 mg cm −3 ) was solubilized in sodium bicarbonate (50 mM) and 1.0 M NaOH was used to adjust the pH to 9.…”
Section: Synthesis Of Dtaf Labeled Sodium Alginatementioning
confidence: 99%
“…Ot is well known that dietary fiber is part of a healthy diet. Studies have shown that the dietary fiber influences the gut physiology and protects against different diseases such as haemorrhoids or cardiovascular disease, atherosclerosis, dyslipidemia, hypertension, and some types of cancer (Kendall et al, 2010;Brownlee, 2011;Mackie et al, 2015;Zhu et al, 2015). Table 2 shows the EAA content of unprocessed and germinated tepary bean flours (UTBF, DGTBF).…”
Section: Chemical Composition and Nutritional Properties Of Optimizedmentioning
confidence: 99%
“…Consumption of a diet with sufficient dietary fiber is recognized as a means of reducing the risk of cardiovascular diseases and diabetes [3,69] . The mechanisms by which these beneficial effects are associated with dietary consumption include increase in viscosity caused by the presence of the fiber (particularly soluble fibers) [4,26,69,70] in the GIT and the ability of the fiber to bind to endogenous enzymes and inhibit their activity [7] . The authors of these studies have associated an increase in viscosity in the presence of fibers in the diet with a reduced rate of gastric emptying, glucose release and absorption.…”
Section: Nutritional Relevance Of Starch Hydrolysis In the Presence Omentioning
confidence: 99%
“…For insoluble fibers such cellulose, it is known that the fiber component physically binds to the enzyme and reduces its availability to degrade starch [7] . In the case of soluble gel forming fibers, such as gums, viscosity is key to the glucose release rate and absorption [26,69] . The relevance of static digestion models in nutrition and food science continues to promote the development and growth static simulated digestion (Table 3).…”
Section: Nutritional Relevance Of Starch Hydrolysis In the Presence Omentioning
confidence: 99%